Single-cell sequencing of neonatal uterus reveals an Misr2+ endometrial progenitor indispensable for fertility - Hatice Duygu Saatcioglu; Motohiro Kano; Heiko Horn; Lihua Zhang; Wesley Samore; Nicholas Nagykery; Marie-Charlotte Meinsohn; Minsuk Hyun; Rana Suliman; Joy Poulo; Jennifer Hsu; Caitlin Sacha; et al. (eLife, 2019)
The Mullerian ducts are the anlagen of the female reproductive tract, which regress in the male fetus in response to MIS. This process is driven by subluminal mesenchymal cells expressing Misr2, which trigger the regression of the adjacent Mullerian ductal epithelium. In females, these Misr2+ cells are retained, yet their contribution to the development of the uterus remains unknown. Here, we report that subluminal Misr2+ cells persist postnatally in the uterus of rodents, but recede by week 37 of gestation in humans. Using single-cell RNA sequencing, we demonstrate that ectopic postnatal MIS administration inhibits these cells and prevents the formation of endometrial stroma in rodents, suggesting a progenitor function. Exposure to MIS during the first six days of life, by inhibiting specification of the stroma, dysregulates paracrine signals necessary for uterine development, eventually resulting in apoptosis of the Misr2+ cells, uterine hypoplasia, and complete infertility in the adult female.